A study on the influence of surface laser texturing on the adhesive strength of bonded joints in aluminium alloys. Issue 1 (2017) - Romoli, L.; Moroni, F.; Khan, M.M.A.
Abstract: The influence of ns-pulsed laser ablation on the adhesive strength of bonded joints was studied under conservative conditions by tensile stress tests on cylindrical specimens of aluminium alloy. Surface textures were produced by hatching the cross section with concentric grooves and varying the average laser power at fixed repetition rate, the scan speed and the radial hatch distance. Despite a range of surface activation in which the adhesive strength increases step-wise of about 25% with respect to the non-treated material, the effect of too high roughness values resulted in a decay of the joint strength. Air entrapment into the ablated grooves fixed a limit to the energy density that could be delivered to the surface, establishing an optimal technology range.